The Elementary Sherlock Holmes Collection - Doyle, Arthur Conan (Saga Egmont, 2022)
From intense deduction methods and trusty sidekicks to supernatural dogs and grizzly murders, ´The Elementary Sherlock Holmes Collection´ offers a generous glimpse into some of the best adventures of the most famous detective of all time. Follow the notorious detective and his companion, Dr Watson, as they try to solve the eerie mystery behind an attempted murder in ´The Hound of the Baskervilles´, or help them solve the mystery of a father gone missing in ´The Sign of the Four´. These are just some of the thrilling adventures included in the collection, which also features the first-ever Sherlock Holmes story ´A Study in Scarlet´ alongside ´His Last Bow´ and ´The Valley of Fear´.Beautifully portrayed by the likes of Benedict Cumberbatch and Robert Downey Jr, Sherlock Holmes has appeared in multiple iterations, most notably as a "high-functioning sociopath" in BBC's ´Sherlock´. With nine exhilarating adventures, ´The Elementary Sherlock Holmes Collection´ serves as the perfect introduction to one of the most famous written characters of all time. It is ideal for fans of "Enola Holmes" on Netflix.-